О скребне Corynosoma arctocephali (Acanthocephala, Polymorphidae) - паразите морского леопарда Hydrurga leptonyx из тихоокеанского сектора Антарктики - Стрюков, А.А. (Вестник зоологии, 2002)
Впервые сообщается о паразитировании акантоцефала Corynosoma arctocephali Zdzitowiecki, 1984 у тюленей тихоокеанского сектора Антарктики. Приведены описание и рисунки исследованных экземпляров. Дано сравнение этого вида с видом C. evae Zdzitowiecki, 1984. Высказано мнение о том, что C. evae и C. arctocephali принадлежат к одному полиморфному виду. The acanthocephal Corynosoma arctocephali Zdzitowiecki, 1984 is recorded for the first time as the parasite of the seals of the Pacific sector of Antarctica. Examined specimens are redescribed and figured. This species is compared to C. evae Zdzitowiecki, 1984. Both C. evae and C. arctocephali are supposed to belong to the same polymorphous species.